Employee participation, firm performance and survival - Pérotin, Virginie; Robinson, Andrew (Emerald, 2004)
This latest volume of Advances contains a series of original and innovative empirical and survey papers that investigate theoretical and contemporary issues facing participatory organizations. The first four papers explore the growing area of participatory and labor-managed firms' survival. The second group of three papers offers a number of new approaches and insights into the performance effects of participatory firms, and the final group of papers provides a broad-ranging synthesis and assessment of the experience of employee ownership and participation in transition economies. Collectively, these nine papers truly constitute Advances in the Economic Analysis of Participatory and Labor-Managed Firms.
Keywords: Management -- Employee participation.; Industrial management -- Employee participation.; elektronické knihy; electronic books